PROBLEMS, TASKS AND MEANS OF REGENERATION OF THE RECENT BELLIGERENT LANDSCAPES OF POST-WAR UKRAINE - Устінова, Ірина; Пєшкова, Олександра (SWorldJournal, 2026)
The article presents the results of an analysis of how the global community perceives Russia’s war against Ukraine at the level of the United Nations and the Parliamentary Assembly of the Council of Europe (PACE) as an act of ecocide against humanity. Em